PERANCANGAN KEMASAN BUBUK KOPI MATAHARI PASAMAN - RAHMAN EFENDI, Dr. M. Nasrul Kamal, M.Sn., Riri Trinanda, S.Pd., M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
This final work is to get an attractive package of coffee powder and can add a new target audience. Through the design of premium packaging, this business is expected to have a visual identity application that is able to attract the attention of the consumer audience so that in the future it can reach a wider target market.This design uses visual communication theory design, media, typography color and layout. Data collection begins with observation, interviews and documentation. Furthermore, the data analysis method used is SWOT (Strenght, Weaknes, Oportuninty, Treatment)Design produces cans and pouches. In addition to the main media is also equipped with several media such as posters, X banners, flyers, car box stickers, aprons, t-shirts, business cards and mugsKata kunci : Desain Kemasan, Promosi,Bubuk Kopi Matahari